In chronic myeloid leukemia white cells from cytogenetic responders and non-responders to imatinib have very similar gene expression signatures - Crossman, Lucy; Mori, Motomi; Hsieh, Yi-Ching; Lange, Thoralf; Paschka, Peter; Harrington, Christina A.; Krohn, Knut; Niederwieser, Dietger W.; Hehlmann, Rüdiger; Hochhaus, Andreas; Druker, Brian J.; Deininger, Michael W. (Haematologica, the hematology journal, 2005)
BACKGROUND AND OBJECTIVES: Imatinib induces complete cytogenetic responses (CCR) in the majority of patients with chronic myeloid leukemia (CML) in chronic phase (CP). However, a subgroup of patients is refractory at the cytogenetic level. Clinically, it would be advantageous to identify such patients a priori, since they may benefit from more aggressive therapy. DESIGN AND METHODS: To elucidate mechanisms underlying cytogenetic refractoriness, we used Affymetrix oligonucleotide arrays to determine the transcriptional signature associated with cytogenetic refractoriness in unselected white blood or bone marrow cells from 29 patients with CML in first CP prior to treatment with imatinib. Patients with CCR within 9 months were defined as responders (n = 16) and patients lacking a major cytogenetic response (> 35% Philadelphia-positive metaphases) after 1 year were defined as non-responders (n = 13). RESULTS: Differences in gene expression between responders and non-responders were subtle. Stringent statistical analysis with multiple comparison adjustments revealed very few differentially expressed genes. Differentially expressed genes could not be confirmed in an independent test set. INTERPRETATION AND CONCLUSIONS: We conclude that transcriptional profiling of unselected white cells is of limited value for identifying genes consistently associated with cytogenetic refractoriness to imatinib.